The role of partnership support in the implementation of corporate farming among independent oil palm smallholders - Vincent Vincent; Diana Chalil; Norfaryanti Binti Kamaruddin (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2026)
The welfare of independent oil palm smallholders in Pelalawan and Siak Regencies, Riau, remains suboptimal because of challenges such as low productivity, weak bargaining power against middlemen, and issues with land legality. As a solution, the government has promoted a farmer corporatization program; however, implementation disparities exist between farmers who partner with companies and those who do not. This study aims to analyze the differences in the implementation of farmer corporatization between partnered and non-partnered independent smallholders and examine the role of partnership in enhancing the success of farmer corporatization. The research was conducted in Kerinci Kiri, Kiah Jaya, and Simpang Beringin Villages, involving 100 respondents (50 partnered and 50 non-partnered farmers) selected using cluster sampling techniques. Data were analyzed using descriptive analysis, difference tests, and simple correlation analysis. The results indicate a significant difference in the implementation of farmer corporatization between the two groups (t = 6.410, p<0.05). Partnered farmers demonstrated superior implementation in terms of management, legality and market access. Furthermore, correlation analysis yielded a coefficient of 0.980 (r = 0.980, p<0.01), indicating that partnerships play a very strong and positive role in the success of farmer corporatization. However, the descriptive findings reveal that existing partnership patterns tend to be top-down with limited participatory planning. In conclusion, while partnership is a primary determinant of the success of farmer corporatization, strengthening managerial aspects and active farmer participation is necessary to achieve sustainable independence.